MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN SENI BUDAYA MATERI TARI DAERAH LAIN MENGGUNAKAN MEDIA VIDEO YOUTOBE KELAS XI SMK NEGERI 3 SUKAWATI - I Nyoman Putrayasa; Gheahni Asti Nadhsiyah (CV. ADIBA AISHA AMIRA, 2023)
This research was conducted with the aim of increasing the achievement or learning outcomes of class XI Tari 1 students at SMK Negeri 3 Sukawati by using YouTube video media in the learning process. Knowing student learning outcomes is very important to improve, this is because learning is said to be successful if student learning outcomes increase. Before the research was conducted, student learning outcomes were low and students found it difficult to understand the material presented by the teacher. The goal to be achieved in this research is to improve the learning outcomes of class XI Tari 1 students at SMK Negeri 3 Sukawati. After doing research, student learning outcomes have increased. Prior to the holding of this research, student learning outcomes were low, students felt the material presented by the teacher was difficult to understand. Cycle I showed an increase, although there were still some students who had not reached the target. Cycle II showed significantly increased student learning outcomes. Based on the results of this study, we recommend teachers to use YouTube video media in the learning process and continue to develop their professional skills in conducting classroom action research. Thus, student learning outcomes can continue to improve and learning can become more effective.